2015
DOI: 10.12659/aot.894878
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival in Hepatocellular Carcinoma Patients

Abstract: Survival was significantly better in patients who underwent liver transplantation or surgical resection. Tumor number, age, and serum albumin level were the most important prognostic factors related to overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Previous studies have shown that contributors to HCC include liver cirrhosis, infection with hepatitis B/C virus (HBV/HCV), adiposity, aflatoxin contamination, excessive alcohol consumption, and environmental pollution [4]. Despite emerging therapies, including percutaneous ablation, liver transplantation, and the recently approved sorafenib (a systemic therapy for HCC), there is still no cure for HCC [1,58]. Therefore, the underlying molecular mechanisms involved in the development of HCC should be further explored to identify innovative therapeutic targets for HCC patients [911].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that contributors to HCC include liver cirrhosis, infection with hepatitis B/C virus (HBV/HCV), adiposity, aflatoxin contamination, excessive alcohol consumption, and environmental pollution [4]. Despite emerging therapies, including percutaneous ablation, liver transplantation, and the recently approved sorafenib (a systemic therapy for HCC), there is still no cure for HCC [1,58]. Therefore, the underlying molecular mechanisms involved in the development of HCC should be further explored to identify innovative therapeutic targets for HCC patients [911].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 72 patients were enrolled during the study period. Clinical and demographic characteristics of the patients were shown in Table 1 , which revealed that recurrence and death all were correlated with hepatitis B surface antigen (HBsAg) expression; interestingly, age (60 years old was taken as cutoff value according to Gokcan’s study 32 ) and tumor stage were related to patients’ death only and seemed to have not any relationship with HCC recurrence; however, the differences of patients’ gender, tumor size (5 cm was considered as cutoff value according to Hwang’s study 33 ), hepatitis B e antigen (HBeAg) levels, histological grade, α-fetoprotein (AFP, 100 ng/dl was identified as cutoff value based on the Brian’s research 34 ) levels, intrahepatic metastasis, hepatic cirrhosis, and lesion location did not appear to have any correlation with prognosis (recurrence and death).…”
Section: Resultsmentioning
confidence: 99%
“…For patient-related factors, age and KPS were identi ed as signi cant prognostic factors in our study and were included as predictors in the model. Advanced age has been widely reported to be associated with poor survival outcomes in HCC, regardless of the staging or therapeutic modes [28,29], but has never been explored in patients with HCC with spinal metastases. Previous studies used a variety of age cut points, ranging from 60 to 70 years old [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age has been widely reported to be associated with poor survival outcomes in HCC, regardless of the staging or therapeutic modes [28,29], but has never been explored in patients with HCC with spinal metastases. Previous studies used a variety of age cut points, ranging from 60 to 70 years old [27][28][29][30]. Our study is the rst one to demonstrate the effect of old age (> 60 years) on the survival of patients with HCC-derived spinal metastases.…”
Section: Discussionmentioning
confidence: 99%